2023
DOI: 10.1177/14680173231180309
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization, stress, and social worker–client relationships during the COVID-19 pandemic

Abstract: Summary The COVID-19 pandemic has dramatically changed the possibilities for people to interact and communicate. This article examines Swedish social workers’ experiences of the extent to which the COVID-19 pandemic has affected the use of digital tools in their work, and whether this use has affected the social worker–client relationship and their stress levels. The article draws on a web survey (N  =  541) via a quantitative analysis of responses and a qualitative analysis of answers to an open-ended questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The Program Keluarga Harapan (PKH) in Indonesia is a significant endeavour that seeks to mitigate poverty and enhance the quality of life for disadvantaged households, serving as a demonstration of the country's dedication to social progress. In order to optimize the efficacy and equitable allocation of PKH benefits, it is crucial to investigate the feasibility of implementing a durable and inclusive monitoring system for the Social Assistance Application [1].…”
Section: Introductionmentioning
confidence: 99%
“…The Program Keluarga Harapan (PKH) in Indonesia is a significant endeavour that seeks to mitigate poverty and enhance the quality of life for disadvantaged households, serving as a demonstration of the country's dedication to social progress. In order to optimize the efficacy and equitable allocation of PKH benefits, it is crucial to investigate the feasibility of implementing a durable and inclusive monitoring system for the Social Assistance Application [1].…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights that digital technologies can revolutionize collaboration in social services and empower professionals to address societal challenges more effectively. It is argued that new digital tools complement face-to-face meetings, enhancing the therapeutic process by providing increased accessibility and flexibility for both social service professionals and applicants (Nordesjö and Scaramuzzino, 2023). Digital technologies have elevated the quality of professionals' core responsibilities regarding applicants, encompassing the collection, recording, and reporting of maximum information.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that they also harbored concerns that the use of digital tools could potentially harm the relationship established with the applicants. It has also been determined that the stress level of social workers using these tools is high (Nordesjö and Scaramuzzino, 2023). Chan (2016) found that there was some uncertainty about the widespread use of technology in social work practices, including protection of professional boundaries and privacy concerns.…”
Section: Introductionmentioning
confidence: 99%